(untitled) (Sound Stage Screen, 2021)
Sweet Land, a new opera by The Industry. February 29–March 15, 2020, Los Angeles State Historic Park. Creative Team: Raven Chacon, Composer; Du Yun, Composer; Aja Couchois Duncan, Librettist; Douglas Kearney, Librettist; Cannupa Hanska Luger, Direc- tor and Costume Designer; Yuval Sharon, Director. Program notes and video streaming available on demand: https://theindustryla.org/sweet-land-opera/.